(3TQM OjhGf TYQ dbjW Hf jYeQ Hf NGQLI GdEjGOis - (3CHi GdefPQ gTGe Hf eMeO Hf GdSGFH GdcdHis; (3dbjW Hf jYeQ Hf NGQLI GdGjGOj,fMh (B250 (3g`s
(3ChdgG (B:s
(3cGfJ EjGO Hf fRGQ JfRd SfOGO ,hSfOGO fgQ ajeG Hjf GdMjQI Edi GdCHdI hcGf Ydjg bUQ JML GdYQH Edjg s
(3BNQgG (B:s
(3agPG eG cGf ef MOjK dbjW hcSQi hZjGO bGd GHf OQjO de Jbd GdYQH bUjOg ai GdfPjQ CLhO ef gPg fLR TYQ dbjW s
(3hdbjW ef TYQGA GdLGgdjg eJhai fMh (B250 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B244 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B157s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B135 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI dGjJhf (B- (3LGeYI YdjcQg (B- (3GdgfO (B((3COH fXe (B11) s
Keywords: (3GdCOHs